Motivation and ICT in Secondary School Mathematics using Unified Theory of Acceptance and Use of Technology Model - Sabainah Oyebola Akinoso (Universitas Pendidikan Indonesia (UPI), 2023)
Mathematics is a special subject that cut across every other subject and every aspect of human life and serves as a clue in solving real-life problems. Teaching mathematics with Information and Communication Technology (ICT) materials might bring tremendous progress in the field of mathematics learning. This is activity-based which makes all students in mathematics class participate fully and contribute to learning. The opinion of secondary school students on ICT use, what is expected from them, and the motivation encountered in mathematics class was investigated. Three hundred (300) secondary school II learners were selected randomly from six secondary schools in Educational District II in Lagos state. The instrument used was based on Mathematics Teaching with ICT (MTICT), this was divided into different sections Student Perceived Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, and Student Motivation. The data were analyzed with percentages and mean. From the result, the use of ICT in teaching secondary school mathematics enhanced the performance expectancy, create more motivation and the social influence from peers, friends, colleagues, and society members contribute immensely to the encouragement of the student in ICT use for studying mathematics. Therefore, ICT should be used in secondary school mathematics teaching.